2008
DOI: 10.1111/j.1365-2648.2007.04568.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term impact of critical illness on relatives: literature review

Abstract: Despite widespread use of the Critical Care Family Needs Inventory, factors such as local or cultural differences may influence relatives' needs. Relatives may also have unidentified needs, and these needs should be explored. Limited research has been carried out into interventions to meet relatives' needs and the effects of critical illness on their well-being, yet some relatives may experience negative psychological consequences far beyond the acute phase of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 70 publications
(164 reference statements)
3
56
0
4
Order By: Relevance
“…Studies on the needs of the family (13) and on the satisfaction towards the care (14)(15) have shown that good communication skills by the ICU team and a flexible visitation policy in the ICU may help relatives in this difficult situation filled with uncertainties (16)(17) .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the needs of the family (13) and on the satisfaction towards the care (14)(15) have shown that good communication skills by the ICU team and a flexible visitation policy in the ICU may help relatives in this difficult situation filled with uncertainties (16)(17) .…”
Section: Resultsmentioning
confidence: 99%
“…De los 30 estudios incluidos en la revisión: uno es un estudio cuasi-experimental 20 , uno es un ensayo no controlado 30 , 3 son revisiones bibliográficas [32][33][34] , uno es un estudio con triangulación múltiple 35 , uno es un estudio con metodología combinada de tipo explicatorio 36 , 3 son observacionales correlacionales transversales 29,31,37 , uno es un estudio observacional comparativo longitudinal 38 , 2 son estudios observacionales comparativos transversales 39,40 y 17 son estudios observacionales descriptivos transversales 5,11,16,17,21,22,28,[41][42][43][44][45][46][47][48][49][50] . En la tabla 3 se adjunta la lista de los artículos incluidos, señalando el objetivo del estudio, el tipo de estudio y el nivel de evidencia que aporta, la muestra utilizada, el cuestionario utilizado y los resultados de mayor interés.…”
Section: Análisis De Los Estudiosunclassified
“…Es más, las revisiones bibliográficas analizadas [32][33][34] lo identifican como el instrumento más utilizado en el ámbito.…”
Section: Análisis De Los Estudiosunclassified
“…This clarity reduces doubts and anxiety. (10)(11)(12) The families feel insecure about the diagnosis, treatment or the multidisciplinary team. They may experience dramatic situations, just like the patients.…”
Section: Introductionmentioning
confidence: 99%